Is it okay to feel this way? Exploring the joint effect of emotional experiences and expectations on life satisfaction - Yeung, June Chun; Roczniewska, Marta; Krys, Kuba (Frontiers in Psychology, 2024)
This research investigates the joint effect of individual emotional experiences and societal expectations on life satisfaction. Inspired by the Affect Valuation Theory and Self-Discrepancy Theory, we explored how discrepancies between actual emotional experiences and what society believes we "ought" to feel are linked with life satisfaction. A total of 301 U.S. online participants rated their emotional experiences and societal expectations for emotions, along with measures of life satisfaction. Response surface analyses were used to assess the effect of emotional experience-norm congruence on life satisfaction. Findings revealed that the highest life satisfaction reported by individuals infrequently experiencing negative emotions but perceiving high societal expectations for these emotions, while congruence effects were not supported. These findings suggest the potential benefits of a societal shift towards greater acceptance of a wider range of negative emotions. The study may potentially stimulate interventions to enhance individuals' life satisfaction by reconsidering societal beliefs about emotions.